Selection of Treatment Regimens for Recurrent Cervical Cancer - Chao, Xiaopei; Song, Xiaochen; Wu, Huanwen; You, Yan; Wu, Ming; Li, Lei (Frontiers in Oncology, 2021)
Objective Selection of an individualized treatment for recurrent cervical cancer remains challenging. This study aimed to investigate the impact of various therapies on survival outcomes after recurrence. Methods Eligible patients were diagnosed with recurrent cervical cancer from March 2012 to April 2018. Postrecurrence progression-free survival (PFS) and overall survival (OS) were investigated in the whole cohort and in subgroups categorized by recurrence site and prior radiotherapy history using a multivariate model, which incorporated treatment for primary and recurrent tumors, histological pathology, and FIGO staging. Results Two hundred and sixty recurrent cervical cancer patients were included. As of March 1, 2020, the median postrecurrence PFS and OS was 7.0 (range 0-94) and 24.0 (1.8-149.1) months, respectively. In a multivariate model, measured by PFS, radiotherapy was superior to other therapies for the whole cohort (p=0.029) and for recurrence only within the pelvic cavity (p=0.005), but the advantages of radiotherapy disappeared in patients with a history of radiotherapy (p values >0.05). For recurrence only beyond the pelvic cavity, combination therapy resulted in improved PFS (p=0.028). For recurrence both within and beyond the pelvic cavity, no therapy regimen provided additional PFS benefits (p values >0.05). Radiotherapy and combination therapy were also associated with improved postrecurrence OS for recurrence within the pelvic cavity (p=0.034) and only beyond the pelvic cavity (p=0.017), respectively.. Conclusions In cervical cancer patients, postrecurrence radiotherapy can improve PFS and OS for patients with recurrence within the pelvic cavity and without prior radiotherapy. For recurrence beyond the pelvic cavity or for cases with a radiotherapy history, combination or individualized therapy may provide potential survival benefits.